1981
DOI: 10.1128/iai.33.1.171-177.1981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the active precipitin components in a purified preparation of the A antigen of Blastomyces dermatitidis

Abstract: A purified A-antigen preparation of Blastomyces dermatitidis was determined to be composed of five major glycoprotein bands, visible with Coomassie blue and periodic acid-Schiff staining of polyacrylamide gels. At least 20 additional protein bands were detected by using a silver stain, which was 100 times more sensitive than the Coomassie method. Two components of this mixture were determined to be associated with the A-antigenic activity of B. dermatitidis. Of several antigen preparations examined in Ouchterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…[ 161, but Hurst and Kaufman [ 131 showed that these epitopes in an A antigen fraction of B. dematitidis were resistant even to rather strong periodate oxidation. Because of the disparity between these two closely related organisms, this study was designed to look for the presence of cross-reactive carbohydrate moieties in the mycoses 40, 83-90 (1997) Young and Larsh [28] showed the presence of five glycoprotein bands in their B. dermatitidis cytoplasmic antigen, which may correspond to the five glycoproteins described here. Unfortunately, these investigators did not determine the molecular masses of the glycoproteins, nor were the bands individually screened for cross-reactivity, so no accurate comparisons could be made with regard to similarities among these components.…”
Section: Discussionmentioning
confidence: 96%
“…[ 161, but Hurst and Kaufman [ 131 showed that these epitopes in an A antigen fraction of B. dematitidis were resistant even to rather strong periodate oxidation. Because of the disparity between these two closely related organisms, this study was designed to look for the presence of cross-reactive carbohydrate moieties in the mycoses 40, 83-90 (1997) Young and Larsh [28] showed the presence of five glycoprotein bands in their B. dermatitidis cytoplasmic antigen, which may correspond to the five glycoproteins described here. Unfortunately, these investigators did not determine the molecular masses of the glycoproteins, nor were the bands individually screened for cross-reactivity, so no accurate comparisons could be made with regard to similarities among these components.…”
Section: Discussionmentioning
confidence: 96%
“…Although the A and ASWS preparations have improved the diagnosis of blastomycosis (4,8), they still contain numerous separate proteins (5,16; K. D. Young and H. W. Larsh, Mycopathologia, in press). It is possible that these polyvalent preparations may lack or obscure important protective or diagnostic components (2).…”
Section: Discussionmentioning
confidence: 99%
“…prepared by mechanical disruption of B. dermatitidis yeast cells in a Braun homogenizer as previously described (16) Okla.). This 009BY preparation was derived from Merthiolate-killed yeast cells of the Centers for Disease Control isolate A 373 and contained 1.0 mg of protein per ml.…”
Section: Materials and Methods Antigen Preparation A Cytoplasmic Framentioning
confidence: 99%
See 2 more Smart Citations